Trends and Spatial Heterogeneity of Climate Extremes in the Southwestern Region of Bangladesh - Tasnima SHIRIN; Tithi SAHA; Md. Hasibur RAHAMAN; Md. Arif CHOWDHURY; Ehsanul BARI; Tusar Kumar DAS; Mohammad Mahfuzur RAHMAN (Chinese Journal of Urban and Environmental Studies, 2022)
This study attempts to investigate the climatic variability in the southwestern area of Bangladesh focusing on temperature and precipitation extremes. Long-term daily records of temperature and precipitation from six weather stations spread over the study area were analyzed. A total of 20 yearly indices were calculated and testified for the trends with the Mann–Kendal test and Sen’s estimator of slope at a 95% confidence interval. Moreover, one-way ANOVA and Tukey–Kramer post-hoc tests were applied to verify the spatial heterogeneity of the climatic indices among the meteorological stations. Findings revealed that Khulna is the worst affected area with significant changes in 12 climatic indices. Jessore and Faridpur followed Khulna with significant changes in 10 and 9 indices, respectively. Among the indices, significant changes in TN10p (frequencies of daily minimum temperature event that falls below the 10th percentile value), TX10p (frequencies of daily maximum temperature event that falls beyond the 10th percentile value), CSDI (cold spell duration indicator), and CDD (consecutive dry day) are the most common phenomenon in the studied region. Five out of six stations have been experiencing significant increasing trends for TN10p. That indicates an overall increase of extreme cold day frequencies in the area. Khulna station showed shreds of evidence of extreme cold temperature instances with a statistically significant fall in the minimum value of the yearly minimum temperatures (TNn). Besides, Khulna also experienced a statistically significant fall in the minimum value of the yearly maximum temperatures. Consistently, the area showed a significant trend of wider cold spells. Similarly, the extremely warm day frequencies have also been increasing significantly for the Khulna, Jessore, and Faridpur areas. Therefore, it is evident that the studied area has been experiencing temperature extremes. On the other hand, precipitation extremes are apparent for only Khulna and Jessore. Both these stations showed increasing trends in heavy precipitation events and wet spells (consecutive precipitation days). ANOVA outcome suggests that the study area has significant spatial heterogeneity in climatic indices. Precipitation indices show high spatial heterogeneity than those of temperature. Among the meteorological stations, Mongla and Ishwardi show the maximum departure than those of others. This study may help policy-makers, researchers, and academicians to take proper initiatives to reduce the impacts of changing climatic parameters in the coastal areas of Bangladesh.